Molecular characterization of coagulation factor XII deficiency in a Japanese family - Wada, Hideo; Nishioka, Junji; Kasai, Yasunari; Kato-Nakazawa, Keiko; Abe, Yasunori; Morishita, Yoshitaka; Nakatani, Kaname; Nobori, Tsutomu (Thrombosis and haemostasis, 2003)
We report the identification in a Japanese family of a novel homozygous W486C mutation in the protease domain of coagulation factor XII (FXII), which was associated with the reduction of plasma FXII activity and antigen level to less than 5% of normal. Sequences of each exon for FXII gene was analysed in family members by polymerase chain reaction (PCR) amplification followed by a direct sequencing method. Sequence analysis showed a homozygous substitution of G to C at nucleotide position 10587 (cDNA position 1458) in proband's FXII gene, resulting in a Trp to Cys substitution in the catalytic domain of FXII. PCR-fragment length polymorphism analysis of 55 healthy volunteers showed no such mutation. Transient expression of FXII in HK-293T cells and analysis of FXII antigen in culture media and cell lysates showed reduced secretion of mutant protein by more than 84% relative to that of wild type protein although the intracellular contents were similar. Our results suggest that the reduced secretion of FXII protein was due to incorrect folding caused by the introduction of Cys486. We designated this mutation as FXII Mie-1.